2023
DOI: 10.1039/d3ra02410e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in fluorescent materials for mercury(ii) ion detection

Abstract: Based on the sensing mechanism, the Hg2+ ion sensing materials developed in recent years were systematically discussed, classified into seven types, and their corresponding fluorescence sensing mechanisms were briefly introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 173 publications
0
7
0
Order By: Relevance
“…Initially, at low Hg 2+ concentrations, the fluorescence is increased due to a fluorescence "on" effect (Scheme S1); however, at higher Hg 2+ concentrations and due to the high RTTA amount in the aerogels, the fluorescence is gradually turned off [51,52]. The fluorogenic switch-off (Scheme S2) sensing of Hg 2+ [31] could be explained by the interruption of the intramolecular conjugation in RTTA molecules through the new interactions established by the nitrogen atoms with Hg 2+ ions. For a more accurate evaluation of the mercury removal efficacy, quantitative methods were employed, which are further described.…”
Section: Hg 2+ Decontamination Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, at low Hg 2+ concentrations, the fluorescence is increased due to a fluorescence "on" effect (Scheme S1); however, at higher Hg 2+ concentrations and due to the high RTTA amount in the aerogels, the fluorescence is gradually turned off [51,52]. The fluorogenic switch-off (Scheme S2) sensing of Hg 2+ [31] could be explained by the interruption of the intramolecular conjugation in RTTA molecules through the new interactions established by the nitrogen atoms with Hg 2+ ions. For a more accurate evaluation of the mercury removal efficacy, quantitative methods were employed, which are further described.…”
Section: Hg 2+ Decontamination Surveymentioning
confidence: 99%
“…Other fluorescent sensors reported for Hg 2+ include the following examples: 1,8-naphthalimide [2], fluorescein [29], BODIPY [30], etc. According to Li Qiuping et al [31], fluorescent sensors frequently utilize multiple sensing mechanisms of Hg 2+ , and their main sensing mechanisms are intramolecular charge transfer, ligand-to-metal energy transfer, static quenching, photoinduced electron transfer, mercury-induced reaction, metallophilic interaction, and aggregation-induced emission. Due to their excellent selectivity, high sensitivity, low cost, accessibility, and suitability for on-site and real-time signaling, fluorescent sensors have become highly sought after in the field of heavy metal ion detection [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, according to the chemical reactions between the receptor and metal cations sensors have received increasing attention due to their good selectivity, and the synthetic probes play a crucial role in the selective determination of specific metal cations. 18–20 Unfortunately, it is generally found that the presence of Ag + or Hg 2+ usually interferes with the detection of the other ions, 21–23 and successful cases in which mercury and silver ions can be identified in the same sensing system are particularly rare because of the similar reaction activities of these two metal ions. 24–27 For example, lots of sensors based on reactions between sulfur-containing receptors and Hg 2+ have been developed due to the high affinity of Hg 2+ towards sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are employed for the detection of mercury, including atomic absorption spectrometry, atomic emission spectrometry, inductively coupled plasma-atomic emission spectrometry, electrochemical analysis, colorimetric methods, and fluorescence analysis [11]. Among these techniques, the fluorescence detection method stands out as extensively utilized for the detection of Hg 2+ ions due to its high sensitivity, selectivity, quick response, cost-effectiveness, and applicability for in vivo detection [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Sensors designed for mercury detection predominantly rely on methods such as fluorescence quenching, fluorescence enhancement, and intramolecular charge transfer processes [11]. Numerous reports detail the detection of mercury based on fluorescence quenching [21][22][23].…”
Section: Introductionmentioning
confidence: 99%